Evaluation of Visual Comfort and Mental Effort Under Different Light Conditions for Ultraviolet-Absorbing and Additional Blue-Filtering Intraocular Lenses for Cataract Surgery - Steinemann, Alexandra; Bromundt, Vivien; Chellappa, Sarah L.; Frey, Sylvia; Schmidt, Christina; Schlote, Torsten; Goldblum, David; Cajochen, Christian (Klinische Monatsblätter für Augenheilkunde, 2019)
Patients and Methods Patients with an ultraviolet blocking lens (UV) (n = 5) or blue filter lens (BB) (n = 8) after intraocular lens (IOL) replacement for cataract and age-adjusted controls (AACs) (n = 16) underwent a balanced crossover within-subject design. After 1.5 h of dark adaptation, they were exposed to polychromatic light at 6500 K (blue-enriched) and 2500 K and 3000 K (non-blue-enriched) for 2 hours in the evening. Visual comfort and mental effort were repeatedly assessed by the Visual Analogue Scale (0 – 100) and the Visual Comfort and Mental Effort Rating Scale (0 – 100) for each light condition. The results were compared using mixed model analysis.Results The mean (± SD) age for AAC and patients with UV or BB was 69.8 ± 6.2 y, 70.8 ± 4 y, and 63.6 ± 5.6 y, respectively. Irrespective of the light condition, patients with UV and BB felt mentally more tired during the experiments compared to AACs (F = 6.15, p = 0.003). However, patients with BB were mentally more motivated to perform the exercises compared to patients with UV and AACs (F = 8.1, p < 0.001). Patients with BB perceived ambient light as less glary (F = 4.71, p = 0.01) than patients with UV. Blue ambient light was felt less intensely in patients with BB (F = 2.51, p = 0.042) compared to those with UV and the AACs.Conclusion Lens replacement in older cataract patients may increase visual comfort and minimize mental effort. While subtle, the magnitude of these effects may depend on the type of intraocular lens. BB intraocular lenses may have potential benefits, as ambient light is perceived as having less glare and less visual tension.
Keywords: cataract; visual comfort; mental effort; intraocular lens; blue filter